In memory of Torgny Vinje - a genuine polar scientist - Isaksson, Elisabeth; Gerland, Sebastian; Divine, Dmitry (Polar Research, 2016)
Keywords: Antarktis; Norsk Polarinstitutt; biografi; forskning; geofysikk; geologi; glasiologi; meteorologi; polarområdene

[Bir kəşfiyyatçı kimi həyatım] - Amundsen, Roald (Alatoran, 2014)
Keywords: Antarktis; biografi; ekspedisjoner; oppdagelsesreiser; polarområdene

[Im kyank’y vorpes beverrayin hetazotogh] - Amundsen, Roald; Movsisyaně, Suren (Toner, 2008)
Keywords: Antarktis; biografi; ekspedisjoner; oppdagelsesreiser; polarområdene

Tilbake til Dronning Maud Land, 45 år etter - Martinsen, Jarle R (Polarboken, 2006)
Keywords: Dronning Maud Land; biografi; ekspedisjoner; historie

Remembering Tore Gjelsvik (1916–2006) - Orheim, Olav (Polar Research, 2006)
Tore Gjelsvik, former director of the Norwegian Polar Institute, died at the beginning of this year. He is fondly remembered by a great many people. In this piece, Olav Orheim recalls the man and his key role in Norwegian polar activities. Orheim was head of Antarctic Research at the Norwegian Polar Institute in 1972–1993 and was the institute’s director from 1993 to 2005.
Keywords: Antarktis; Norsk Polarinstitutt; biografi; geologi; polarområdene

Sydpolen - Skog, Cecilie; Sandberg, Sigri (Cecilie Skog og de tre polene, 2006)
Keywords: Antarktis; Sydpolen; Sørpolen; biografi; ekspedisjoner; reiser; reiseskildringer